Assessing the Impact of Weak and Moderate Geomagnetic Storms on UK Power Station Transformers - Z. M. Lewis; J. A. Wild; M. Allcock; M.‐T. Walach (Space Weather)
Abstract It is well documented that space weather can impact electricity infrastructure, and several incidents have been observed in recent decades and directly linked to large geomagnetic storms (e.g., the Hydro Québec incident in 1989). However, less is understood about the impact of lower‐level geomagnetically induced currents on the health of transformers in the long term. In this study, the long term impact of geomagnetic activity on 13 power station transformers in the UK is investigated. Dissolved gas measurements from 2010 to 2015 were used to look for evidence of a link between degradation of the transformer and heightened levels of the global SYM‐H index and dBdt as measured at Eskdalemuir magnetometer station in southern Scotland. First, case studies of the most significant storms in this time period were examined using dissolved gas analysis methods, specifically the Low Energy Degradation Triangle. These case studies were then augmented with a statistical survey, including Superposed Epoch Analysis of multiple storm events. No evidence of a systematic space weather impact can be found during this time period, likely owing to the relatively quiet nature of the Sun during this epoch and the modernity of the transformers studied.